The Effect of Employee Morale and Organizational Familiarity on Innovative Work Behavior through Employee Engagement - Ika Puspa Satrianny; Thamrin; Nasib; Adi Harianto; Emma Novirsari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the influence of employee morale and organizational familiarity on innovative work behavior, with employee engagement serving as a mediating variable. The research contributes to the organizational behavior literature by integrating motivational and contextual factors to explain innovative behavior among employees, particularly within the context of an Indonesian manufacturing company, PT. Karya Lencana Mas. The study aims to investigate both the direct and indirect effects of employee morale and organizational familiarity on innovation through employee engagement. Using a quantitative approach, data were collected through structured questionnaires distributed to employees with a minimum of one year of service. The data were then analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings indicate that both employee morale and organizational familiarity have significant effects on innovative work behavior, both directly and indirectly through employee engagement. Employee engagement plays a crucial mediating role in strengthening these relationships. These findings highlight the importance of creating a positive work environment and enhancing employees’ understanding of organizational systems and culture. The practical implications of this study suggest the need for HR strategies and leadership practices that focus on improving employee morale and organizational socialization to foster a more engaged and innovative workforce.